2022
DOI: 10.1037/apl0000903
|View full text |Cite
|
Sign up to set email alerts
|

Being present and thankful: A multi-study investigation of mindfulness, gratitude, and employee helping behavior.

Abstract: Gratitude plays an integral role in promoting helping behavior at work. Thus, cultivating employees' experiences of gratitude represents an important imperative in modern organizations that rely on teamwork and collaboration to achieve organizational goals. Yet, today's workplace presents a complex array of demands that make it difficult for employees to fully attend to and appreciate the various benefits they receive at work. As such, gratitude is difficult for employers to promote and for employees to experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 154 publications
(265 reference statements)
2
61
0
1
Order By: Relevance
“…Keywords which have received recent citation bursts also illuminate some emerging trends. Gratitude, which has been called one of the "sisters of mindfulness" (Rosenzweig, 2013), seems to have attracted renewed interest within mindfulness literature (Sawyer et al, 2021;Swickert et al, 2019). The ability of mindfulness to reduce loneliness also appears to have gained recognition; this probably reflects the ongoing need for interventions to combat loneliness in the context of the COVID-19 pandemic (Teoh et al, 2021).…”
Section: Recent Trendsmentioning
confidence: 99%
“…Keywords which have received recent citation bursts also illuminate some emerging trends. Gratitude, which has been called one of the "sisters of mindfulness" (Rosenzweig, 2013), seems to have attracted renewed interest within mindfulness literature (Sawyer et al, 2021;Swickert et al, 2019). The ability of mindfulness to reduce loneliness also appears to have gained recognition; this probably reflects the ongoing need for interventions to combat loneliness in the context of the COVID-19 pandemic (Teoh et al, 2021).…”
Section: Recent Trendsmentioning
confidence: 99%
“…This is broadly consistent with previous research showing relationships between some of these constructs, although no previous research has examined the relationships between all four of these constructs. For example, Sawyer et al [ 84 ] found evidence of an indirect effect between mindfulness, perspective taking (the cognitive capacity to consider the viewpoint of others, similar to the cognitive flexibility construct included in The Resilience Shield model) and gratitude. Locus of control has also been shown to be associated with gratitude and mindfulness, with individuals with a more internal locus of control having a greater disposition for gratitude and mindfulness [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Managers may foster these positive connections for employees by providing them with emotional support during stressful times during the day or by building a team where its members willingly provide task assistance to each other (Colbert et al, 2016). Organizations can introduce mindfulness training for employees to help them better capture PA from positive experiences by reflecting on good things that employees experience throughout the day or the week (Sawyer et al, 2021) and by sharing them with others (Gable et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Organizations can introduce mindfulness training to minimize the magnitude of reactions to daily negative events (Good et al, 2016). Since negative interactions with customers and coworkers contribute a large part to employees' NA throughout the day and the day after (Tremmel & Sonnentag, 2018), mindfulness training may encourage employees to take customers' and coworkers' perspectives, which may help them minimize the magnitude of reactions to daily negative events (Sawyer et al, 2021) and help them with effective coping (Folkman & Moskowitz, 2000; Larsen & Prizmic, 2008). If organizations are aiming to improve employee health and reduce healthcare costs, our data suggest that decreasing NA and increasing PA are effective.…”
Section: Discussionmentioning
confidence: 99%